The Information Content of IPO Prospectuses - Hanley, Kathleen Weiss; Hoberg, Gerard (Review of Financial Studies, 2010)
Using word content analysis, we decompose information in the initial public offering prospectus into its standard and informative components. Greater informative content, as a proxy for premarket due diligence, results in more accurate offer prices and less underpricing, because it decreases the issuing firm's reliance on bookbuilding to price the issue. The opposite is true for standard content. Greater content from high reputation underwriters and issuing firm managers, through Management's Discussion and Analysis, contribute to the informativeness of the prospectus. Our results suggest that premarket due diligence and disclosure by underwriters and issuers can serve as a substitute for costly bookbuilding. The Author 2010. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oxfordjournals.org., Oxford University Press.